Jus Cogens: Problem of the Role in Treaty Interpretation - Karvatska, Svitlana (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
Due to their specific legal nature, the jus cogens rules occupy a special place and have conceptual significance in international law system in the vein that their non-compliance may, in fact, sabotage foundations of the international legal system based on states consent. Since the entry into force of the VCLT, jus cogens concept in international law has moved closer to international legal practice. A paradoxical situation exists - jus cogens concept in international law is generally accepted, there is also a normatively established definition of such a rule, but its specific framework and content remain unclear. The ICJ has repeatedly addressed the issue of jus cogens norms, but a detailed concept on jus cogens has not been formed. It is analyzed that the problem of establishing jus cogens is difficult to solve in abstractio. The reason lies not only in the absence of a single official list of norms jus cogens – the criteria for including norms in such a list are not defined. Opinions of representatives of the doctrine and the international judiciary on this issue differ significantly. Addressing the problem of the role and significance of jus cogens, general international law imperative rules, for the observance and interpretation of treaties, it should be noted that treaties are to be interpreted in a format compatible with the imperative norms. The considerations presented in the research indicate a special, if not decisive, role in the observance of jus cogens in treaties interpretation.Keywords: International Law; VCLT; Treaties; Imperative Rules Jus Cogens: Masalah Peran dalam Interpretasi Perjanjian AbstrakAturan Jus Cogens menempati tempat khusus dan memiliki makna konseptual dalam sistem hukum internasional dikarenakan sifat hukumnya yang spesifik, selain karena ketidakpatuhannya dapat menyabot fondasi sistem hukum internasional berdasarkan persetujuan negara. Sejak berlakunya VCLT, konsep Jus Cogens dalam hukum internasional semakin mendekati praktik hukum internasional. Situasi paradoks terjadi - konsep Jus Cogens dalam hukum internasional diterima secara umum. Ada juga definisi yang ditetapkan secara normatif dari aturan semacam itu, tetapi kerangka kerja dan isinya yang spesifik masih belum jelas. ICJ telah berulang kali membahas masalah norma Jus Cogens, tetapi konsep rinci tentang Jus Cogens belum terbentuk. Dianalisis bahwa masalah pembentukan Jus Cogens sulit dipecahkan secara abstrak. Alasannya tidak hanya terletak pada tidak adanya satu daftar resmi norma Jus Cogens – kriteria untuk memasukkan norma dalam daftar tersebut tidak didefinisikan. Pendapat perwakilan doktrin dan peradilan internasional tentang masalah ini berbeda secara signifikan. Mengatasi masalah peran dan pentingnya Jus Cogens, aturan umum hukum internasional imperatif, untuk ketaatan dan interpretasi perjanjian. Perlu dicatat bahwa perjanjian harus ditafsirkan dalam format yang kompatibel dengan norma-norma imperatif. Pertimbangan yang disajikan dalam penelitian ini menunjukkan peran khusus, jika tidak menentukan, dalam ketaatan Jus Cogens dalam interpretasi perjanjian.Kata kunci: Hukum Internasional; VCLT; Perjanjian; Aturan Imperatif Jus Cogens: Проблема Роли В Толковании Договора Aннотация Нормы jus cogens вследствие своей специфической правовой природы занимают особое место, имеют концептуальное значение в системе международного права в том смысле, что их несоблюдение может фактически подорвать основы международной правовой системы, которая опирается на согласие государств. Со времени своего включения в Венскую конвенцию о праве международных договоров 1969 г., концепция международного права jus cogens подошла к международной юридической практике. Доказано, что имеет место парадокс – концепция jus cogens в международном праве общепринятая, также существует нормативно-закрепленное понятие такой нормы, при этом ее рамки и содержание остаются неточными. МС ООН неоднократно касался проблематики норм jus cogens, однако не дал системного видения данного вопроса. Проблему определения jus cogens решить in abstracto сложно. Причина не только в отсутствии единого официального перечня норм jus cogens – не определены критерии включения норм в такой перечень. Мнения представителей доктрины и международного судейского корпуса по этому поводу существенно различаются. Приведенные в исследовании соображения свидетельствуют об особой, если не решающей, роли jus cogens в процессе интерпретации международных договоров.Ключевые слова: Jus cogens, международное право, интерпретация международных договоров, ВКПМД